Transport and Storage means for avulsed teeth - Quintana del Solar, Carmen Inocencia (2007)
A review of the literature was made regarding the way avulsed teeth were stored. An online search in Medline was used, including those publications between 1980 and 2007 in which the key word: “viability”, “storage medium”, “storage media”, “tooth avulsion” and “avulsion” appeared. The best storages are those that have the following characteristics: pH and physiological osmolality, contain nutrients, are liquid sterile and are available at the moment of the accident. The results of those studies showed that low-fat fresh milk pasteurized was better than saliva, water, contact lens solutions and the Gatorade®. HBSS and Viaspan were better than milk, propolis and tender Coconut water. Viaspan was equal to, or better than, HBSS in preserving periodontal ligament cells. Unfortunately, despite of its effectiveness in maintaining periodontal ligament cells viability, Viaspan and HBSS are expensive and are not available like milk.